Natural polymers for pharmaceutical applications. Volume 3, Animal-derived polymers - Nayak, Amit Kumar, 1979-; Hasnain, Md Saquib, 1984-; Pal, Dilipkumar, 1971- ([New York] : Apple Academic Press, 2019)
In recent years, many animal-derived polymers have emerged as an attractive category of naturally derived polymers because of their advantageous physicochemical, chemical, and biological properties. The important biological properties of these natural polymers derived from animals are biocompatibility and biodegradation. These polymers are generally composed of repeated units of amino acids. Moreover, these polymers can be modified physically and/or chemically to improve their biomaterial properties. Natural Polymers for Pharmaceutical Applications, Volume 3: Animal-Derived Polymers looks at how these polymers can be exploited as pharmaceutical excipients in various pharmaceutical dosage forms, like microparticles, nanoparticles, ophthalmic preparations, gels, implants, etc. The commonly used animal-derived polymers used as pharmaceutical excipients are hyaluronic acid (hyaluronan), albumin, collagen, gelatin, chondroitin, etc.
Volume 3: Animal-Derived Polymers 1. Hyaluronic Acid (Hyaluronan): Pharmaceutical Applications Amit Kumar Nayak et al. 2. Pharmaceutical Applications of Albumin Suvadra Das and Partha Roy 3. Pharmaceutical Applications of Collagen K. Sangeetha et al. 4. Pharmaceutical Applications of Gelatin Gautam Singhvi et al. 5. Pharmaceutical Applications of Chondroitin Dilipkumar Pal et al. 6. Biodegradability and Biocompatibility of Natural Polymers Abul K. Mallik et al.
OCLC-licensed vendor bibliographic record.
Keywords: Polymers in medicine; Biopolymers; Pharmaceutical technology